2017
DOI: 10.1111/asj.12950
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormones alter estrous cyclicity and antioxidative status in the ovaries of rats

Abstract: To expand our understanding of the roles of thyroid hormones on female reproduction, we induced hypo- and hyper-T rat models to investigate the roles of thyroid hormones on estrous cyclicity, as well as the antioxidative status in the ovaries of rats. In the current study, our data show that hypothyroidism (hypo-T) and hyperthyroidism (hyper-T) led to significantly reduced body weights and ovarain weights and delayed vaginal opening day. For hyper-T, thyroxine (T4), tri-iodothyronine (T3), progesterone (P4) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 66 publications
2
12
0
Order By: Relevance
“…We found that T4 diminished serum 17β‐estradiol accumulation (end product of synthesis, secretion and metabolism) by porcine granulosa cells. Our previous studies showed that the production of 17β‐estradiol was significantly decreased in both hypothyroid and hyperthyroid treatments (Wei et al, ). We hypothesized that thyroid hormone abnormalities would disturb sexual hormone secretion so as to affect reproductive performance in animals.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…We found that T4 diminished serum 17β‐estradiol accumulation (end product of synthesis, secretion and metabolism) by porcine granulosa cells. Our previous studies showed that the production of 17β‐estradiol was significantly decreased in both hypothyroid and hyperthyroid treatments (Wei et al, ). We hypothesized that thyroid hormone abnormalities would disturb sexual hormone secretion so as to affect reproductive performance in animals.…”
Section: Discussionmentioning
confidence: 96%
“…Our previous data also revealed that thyroxine (T4) plays important roles in follicular development in the ovaries of postnatal and immature rats (Fedail et al, ), and we therefore used T4 in the present study. In addition, this dose of T4 was chosen according to our previous study (Wei et al, ), where we measured total T3 and T4 levels and T3/T4 ratios in the serum of control, hyper‐T and hypo‐T rat on day 80. Furthermore, this dose range is similar to that used in previous studies (Asahara, Sato, Aljonaid, & Maruo, ; Chan & Tan, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have revealed that thyroid hormones alter estrous cyclicity and antioxidative status in the ovary of the rat acting through the nitric oxide synthase signaling pathway ( Zheng et al, 2015 ; Wei et al ., 2018 ). It was also reported that ovarian follicles of the laying hen express mRNAs of thyroid hormone-nuclear receptors, as well as integrin (αVβ3) plasma membrane receptors, indicating a genomic and non-genomic action of thyroid hormones in the chicken ovary ( Sechman, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are reports that the thyroid state modulates the expression of antioxidant enzymes in various tissues [1416]. However, the effect of TH on the regulation of the expression of antioxidant enzymes and the cellular redox state in the lymphoid tissue has not yet been clarified.…”
Section: Introductionmentioning
confidence: 99%